2015
DOI: 10.1177/0956797614560648
|View full text |Cite
|
Sign up to set email alerts
|

Amnesia for Object Attributes

Abstract: People intuitively believe that when they become consciously aware of a visual stimulus, they will be able to remember it and immediately report it. The present study provides a series of striking demonstrations of behavior that is inconsistent with such an intuition. Four experiments showed that in certain conditions, participants could not report an attribute (e.g., letter identity) of a stimulus even when that attribute had been attended and had reached a full state of conscious awareness just prior to bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 40 publications
6
72
1
Order By: Relevance
“…A recent study (Chen & Wyble, 2015) asked a question similar to ours, but did not use crowdsourcing. Subjects viewed a brief display consisting of three numbers and one letter, each with a different color.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Chen & Wyble, 2015) asked a question similar to ours, but did not use crowdsourcing. Subjects viewed a brief display consisting of three numbers and one letter, each with a different color.…”
Section: Discussionmentioning
confidence: 99%
“…That is, although the participants were informed to ignore the irrelevant feature, they noticed the change of the irrelevant feature during the practice or formal experiment and deduced that it could be task-relevant and therefore changed their processing strategy. Supporting this possibility, Chen and Wyble 21 recently revealed that once the participants noticed the test content, they changed their processing strategy immediately. Therefore, an Achilles’ heel may be hidden in previous studies employing the irrelevant-change distracting effect, which represents a severe challenge to the established OBE in VWM.…”
mentioning
confidence: 94%
“…In particular, there is evidence that people can selectively encode and maintain a subset of task-relevant features of an attended object and filter out the remaining task-irrelevant features (e.g., Eitam, Yeshurun & Hassan, 2013 ; Triesch et al, 2003 ; Woodman & Vogel, 2008 ). More recently, it has been shown that observers will often be unable to report features of an attended object that are task-relevant but that the observers did not expect to report, a phenomenon referred to as attribute amnesia ( Chen & Wyble, 2015 ; Chen & Wyble, 2016 ). This challenges the common assumption that information in the focus of attention that has reached access awareness ( Lamme, 2004 ) should always be reportable immediately after its presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Following Kanwisher & Driver (1992) , attribute amnesia studies have used the term attribute broadly to refer to any aspect (e.g., colour, location, identity) of a visual stimulus ( Chen & Wyble, 2015 ; Chen & Wyble, 2016 ). A typical attribute amnesia experiment starts with an observer performing a number of trials in which they are asked to recall one aspect of a target stimulus before being unexpectedly asked to recall a different aspect of the target stimulus on the “surprise” trial.…”
Section: Introductionmentioning
confidence: 99%